Graphical representation of attacks on security protocol - Wang, Jianfang (2016)
In a digital age, cryptographic security protocols are extremely important in ensuring a secure communication in an open network. Many research has arise in the field of protocol design and verification. However, verification of protocol can be extremely difficult to be done manually. With massive amount of protocol begin design it make the verification more difficult. Thus, automate verification tools such as Proverif is developed to aid, the verification process. But Proverif output maybe can be very complex for a new user to understand. In this project, its aim to aid the new user in understanding the output of Proverif through the conversion of output text to graphical representation. The protocol notation was use to convert to Proverif output, this result is then parse and generate into graphical representation. The graphical representation generate from output text may not be exactly match to the claimed attack of example protocol. But it is able to provide user an addition perspective of the attack, and ease the message tracing and back tracing while understanding the output.